A Study on the Creep Characteristics of Airport Viscous Subsoil Based on Unsaturated Stress Level. (15th January 2021) - Feng, Jun; Ma, Yue; Liu, Zaobao
Abstract : The present study takes the ratio of the matric suction to the net vertical stress and the ratio of the matric suction to the net mean stress as new unsaturated stress levels f and F, respectively. Based on the laboratory tests and theoretical derivation, the modified one-dimensional Mesri creep model and three-dimensional creep model were established, which takes the unsaturated stress level into account. Then, the one-dimensional and three-dimensional creep characteristics of the unsaturated viscous subsoil of an airport under different unsaturated stress levels were analyzed. The following conclusions could be drawn: (1) under different stress levels, the one-dimensional creep deformation of unsaturated soil has a power function relationship with time, and the change rate exponentially decreases with the stress level, which can be well-expressed by the proposed modified one-dimensional Mesri creep model; (2) under different stress levels, the three-dimensional creep strain of the unsaturated soil shows a hyperbolic curve with time and a near-linear relationship at the semilogarithmic coordinate, which can be well-expressed by the proposed modified three-dimensional creep model; (3) under different stress levels, both the one-dimensional creep and three-dimensional creep of the unsaturated soil can be divided into two stages, which are the accelerated creep stage and stable creep stage.